Black Orpheus : music in African American fiction from the Harlem Renaissance to Toni Morrison - Simawe, Saadi (New York : Garland Pub., 2000)
In twentieth-century African American fiction, music has been elevated to the level of religion primarily because of its power as a medium of freedom. This collection explores literary invocations of music.
Series editor's foreword / Daniel Albright -- Introduction: the agency of sound in African American fiction / Saadi A. Simawe -- Singing the unsayable: theorizing music in Dessa Rose / Jacquelyn A. Fox-Good -- Claude McKay: music, sexuality, and literary cosmopolitanism / Tom Lutz -- Black moves, white way, every body's blues: orphic power in Langston Hughes's The ways of white folks / Jane Olmsted -- Black and blue: the female body of blues writing in Jean Toomer, Toni Morrison, and Gayl Jones / Katherine Boutry -- That old black magic? Gender and music in Ann Petry's fiction / Johanna X.K. Garvey -- "It don't mean a thing if it ain't got that swing": jazz's many uses for Toni Morrison / Alan J. Rice -- Shange and her three sisters "sing a liberation song": variations on the orphic theme / Maria V. Johnson -- Nathaniel Mackey's unit structures / Joseph Allen -- Shamans of song: music and the politics of culture in Alice Walker's early fiction / Saadi A. Simawe.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: American fiction -- African American authors -- History and criticism; American fiction -- 20th century -- History and criticism; Music and literature -- History -- 20th century; African Americans -- Music -- History and criticism; Musical fiction -- History and criticism; African American musicians in literature; African Americans in literature; Music in literature; Roman américain -- Auteurs noirs américains -- Histoire et critique; Roman américain -- 20e siècle -- Histoire et critique; Musique et littérature -- Histoire -- 20e siècle.; Noirs américains -- Musique -- Histoire et critique; Musiciens noirs américains dans la littérature.; Noirs américains dans la littérature.; Musique dans la littérature.; Roman musical -- Histoire et critique; LITERARY CRITICISM -- American -- General; African American musicians in literature; African Americans in literature; African Americans -- Music; American fiction; American fiction -- African American authors; Music and literature; Music in literature; Musical fiction; Literatur; Musik; Aufsatzsammlung; Schwarze; USA; Schwärze; 1900-1999; Geschichte 1920-1995.; Electronic books; Criticism, interpretation, etc; History